The Influence of Digital Artificial Intelligence Technology on Quality of Life with a Global Perspective - Sandy Kosasi; Chandra Lukita; Mochamad Heru Riza Chakim; Adam Faturahman; Dhiyah Ayu Rini Kusumawardhani (Aptisi Transactions On Technopreneurship (ATT), 2023)
The rapid development of digital technology and artificial intelligence (AI) has brought significant changes in many areas of life, including business, healthcare, education, and entertainment. The great potential of AI technologies to provide positive benefits to society is balanced with concerns about their negative impact on quality of life. This study aims to explore the influence of digital AI technology on the overall quality of life around the world, focusing on the Performance Expectancy, Effort Expectancy, and Use Behavior aspects of digital AI technology. This research method utilizes the UTAUT (Unified Theory of Acceptance and Use of Technology) approach and collects data quantitatively through a questionnaire covering 3 variables related to digital AI technology and its influence on quality of life. Data analysis was conducted using PLS-SEM (Partial Least Squares - Structural Equation Modeling) to identify important aspects related to the advantages and disadvantages of AI technology. The results from the 70 respondents indicated that digital AI technologies have the potential to improve quality of life by meeting performance expectations and providing ease of use, and a balanced approach is needed in the development and implementation of AI technologies to maximize their positive impact while minimizing their negative impact.